1996
DOI: 10.1164/ajrccm.153.5.8630622
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar lavage in adult sickle cell patients with acute chest syndrome: value for diagnostic assessment of fat embolism.

Abstract: Fat embolism of necrotic bone marrow could be a frequent cause of acute chest syndrome (ACS) in sickle cell syndromes (SC), as suggested by postmortem findings. To check this hypothesis in living patients, we evaluated the presence of fatty macrophages recovered by bronchoalveolar lavage (BAL) in ACS. We investigated 20 consecutive cases of ACS by BAL, and identification of alveolar cells containing fat droplets was performed using oil red O (ORO), a specific neutral fat stain. The specificity of the method wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
2
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 19 publications
4
67
2
7
Order By: Relevance
“…As macrophages act as lung scavengers, they might be expected to contain fat in FES. BAL in trauma patients has been proposed as a specific method for diagnosing FES within the first 24 h [22,23]. However, there are difficulties in obtaining satisfactory samples, as shown in one study where only 67 out of 96 samples were adequate for analysis due to low yield of macrophages [24].…”
Section: Q 2001 Blackwell Science Ltdmentioning
confidence: 99%
See 2 more Smart Citations
“…As macrophages act as lung scavengers, they might be expected to contain fat in FES. BAL in trauma patients has been proposed as a specific method for diagnosing FES within the first 24 h [22,23]. However, there are difficulties in obtaining satisfactory samples, as shown in one study where only 67 out of 96 samples were adequate for analysis due to low yield of macrophages [24].…”
Section: Q 2001 Blackwell Science Ltdmentioning
confidence: 99%
“…FES is recognised as part of an acute sickle cell crisis [17,23,56]. Acute chest syndrome is the second most common reason for hospital admission and leading cause of death in sickle cell disease.…”
Section: Predispositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially Streptococcus pneumoniae was considered the most common infectious agent, 9,10 but subsequent research has consistently reported lower rates of pneumococcal disease. 2,7,[11][12][13][14][15] This apparent change may be the result of more rigorous research methodology or therapies developed specifically to prevent pneumococcal disease such as prophylactic penicillin and vaccine administration. 13,16,17 Chlamydia pneumoniae and Mycoplasma pneumoniae are now the most common documented infectious causes of ACS.…”
Section: Infectionmentioning
confidence: 99%
“…7,13,18,19 Other viral and bacterial organisms that have been linked to ACS include Haemophilus influenzae, Staphylococcus aureus, Klebsiella pneumoniae, adenovirus, influenza viruses, parainfluenza viruses, respiratory syncytial virus, parvovirus B19, and cytomegalovirus. 6,7,[9][10][11][12][13][14][15][18][19][20] …”
Section: Infectionmentioning
confidence: 99%